“Mortality trends and geographic distribution of kidney cancer in Peru: a secondary analysis“ - Torres-Roman, J. Smith (2023)
“Background The incidence of kidney cancer has been increasing worldwide, with variable patterns in mortality due to improved diagnostic techniques and increased survival. The mortality rates, geographical distribution and trends of kidney cancer in South America remain poorly explored. This study aims to illustrate mortality by kidney cancer in Peru. Methods A secondary data analysis of the Deceased Registry of the Peruvian Ministry of Health database, from 2008 to 2019 was conducted. Data for kidney cancer deaths were collected from health facilities distributed throughout the country. We estimated age-standardized mortality rates (ASMR) per 100,000 persons and provided an overview of trends from 2008 to 2019. A cluster map shows the relationships among 3 regions. Results A total of 4221 deaths by kidney cancer were reported in Peru between 2008 and 2019. ASMR for Peruvian men ranged from 1.15 to 2008 to 1.87 in 2019, and from 0.68 to 2008 to 0.82 in 2019 in women. The mortality rates by kidney cancer rose in most regions, although they were not significant. Callao and Lambayeque provinces reported the highest mortality rates. The rainforest provinces had a positive spatial autocorrelation and significant clustering (p<0.05) with the lowest rates in Loreto and Ucayali. Conclusion Mortality by kidney cancer has increased in Peru, being a trend that disproportionally affects more men than women. While the coast, especially Callao and Lambayeque, present the highest kidney cancer mortality rates, the rainforest has the lowest rates, especially among women. Lack of diagnosis and reporting systems may confound these results.“